International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law (Human Rights – Children’s Rights, 2026)
The book serves as a textbook for the Human Rights and Rule of Law LL.M. programme on the first place. As its title – International Criminal Law, Humanitarian Law and Refugee Law from the Perspective of Human Rights Law – suggests, the volume focuses on those branches of international public law that are closely related to human rights law, and assists readers in getting a comprehensive overview on supplementary but significant segments of international public law that might also come into play when it comes to discussing and solving human rights problems. Therefore, the book primarily serves educational purposes to navigate Human Rights and Rule of Law LL.M. students in understanding the key definitions and fundamental functioning of international human rights law’s border areas; (in synthesising their previously acquired knowledge on human rights; in introducing supplementary definitions that are of special significance when facing human rights issues; and all in all, in giving a whole landscape on these inter-related segments of international public law, in addition to granting considerable and complex knowledge on human rights. Thus, the ultimate aim of this book is to provide the readers with a thorough analysis on certain branches of international public law that have a strong relationship with international human rights law: international criminal law, international humanitarian law and international refugee law. Throughout the pages of this book, an overview is offered on the history of international criminal law, on international crimes, on the International Criminal Tribunal for the Former Yugoslavia and the International Criminal Tribunal for Rwanda, on the International Criminal Court, on the history of humanitarian law, on the principles of humanitarian law (the principle of humanity, the principle of military necessity, the principle of distinction and the principle of proportionality), on the 1949 Geneva Conventions and their Additional Protocols I-III, on the distinction between migration law and refugee law as well as between the terms of “migrant” and “refugee”, on the 1951 Convention Relating to the Status of Refugees, on the principle of non-refoulement, and on some specific Central and Eastern European characteristics.